Clinical status of COVID-19 vaccinated pregnant women: an observational study in a tertiary care hospital in Bangladesh - Akhter, Hasina; Yasmin, Shamima; Nahar, Kamrun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pregnancy is a special but often stressful time. The COVID-19 pandemic exacerbated this stress. Clinical trials have demonstrated the safety of COVID-19 vaccines for pregnant and lactating women, leading to WHO approval. Consequently, the Bangladesh Government has initiated a vaccination campaign for all expectant mothers to protect them from COVID-19. This study aimed to assess the clinical status of COVID-19-vaccinated pregnant women. Methods: A cross-sectional study was carried out at Department of Obstetrics & Gynaecology in Combined Military Hospital, Dhaka Cantonment, Bangladesh, spanning August to November 2021. The study included 50 pregnant women who had received COVID-19 vaccinations, selected through purposive sampling. Data analysis and dissemination were performed using MS Office tools. Results: The study found that the average age was 19.2±10.8 years, with 66% falling into the 25-35 age group. About 50% had a normal BMI, while 22% were overweight (BMI: 25.0-29.9 Kg/m2). Hypertension and diabetes were present in 16% and 12% of cases, respectively. Among the 50 pregnant women, 40% were nulliparous, and 60% were multiparous; in most of the cases (54%), multigravidity (1-5) was found. Vaccination distribution was 28% in the 1st trimester, 54% in the 2nd, and 18% in the 3rd trimester. Conclusions: COVID-19 vaccination rates are notably higher among pregnant women aged 25-35. The frequency of normal BMI among COVID-19-vaccinated pregnant women is satisfactory. Most pregnant women opt for COVID-19 vaccination during their second trimester.